What Is Open Pedagogy? Identifying Commonalities - Tietjen, Phil; Asino, Tutaleni I. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2021)
Open pedagogy has been touted by advocates as a promising expansion of open educational resources because it involves shifting from making resources accessible to impacting the practice of teaching. The allure of the term coupled with its promise to bring greater innovation to pedagogy has led to its widespread use at conferences and publications. However, as the concept has gained increasing levels of popularity, it has also sparked considerable debate as to what it means. For example, how is open pedagogy distinct from other forms of pedagogy such as critical or cultural? What does it mean to practice open pedagogy? Without a clear understanding of its meaning, establishing a solid research foundation on which to make claims about the impact of open pedagogy approaches is difficult. Accordingly, this article argues that the current debate signals the need for the development of robust analytical frameworks in order to construct a cohesive body of research that can be used to advance it as a field of study. To do this, the authors review the literature and identify common characteristics within it. The authors then propose a five-part framework that encourages the long-term sustainability of open pedagogy.